Food environment with high plant-based fat supply is associated with Attention-Deficit/Hyperactivity Disorder (ADHD) protection: a global study with more than 150 countries - Ni, Duan; Senior, Alistair; Raubenheimer, David; Simpson, Stephen J.; Nanan, Ralph (Frontiers in Nutrition, 2025)
BackgroundDiet and nutrients are emerging key players in neurological disorders. Attention-Deficit/Hyperactivity Disorder (ADHD) is a major neurodevelopmental disorder on a global scale, affecting children and increasingly being recognized and diagnosed in adult populations. While its aetiology is unclear, it appears to involve a combination of genetic and environmental factors, particularly food environments including diets and nutrients. However, most studies so far have focused on the impacts of individual nutrients or dietary patterns on clinically established ADHD. In contrast, the interactive effects of diets and nutrients and their complex interplay with other factors like socioeconomic status on ADHD prevalence and incidence have so far been overlooked. Here, we aim to systematically interrogate the association between nutrient supply, reflecting the food exposure and dietary environment, socioeconomic status and ADHD disease prevalence and incidence at a global level over time.MethodsADHD disease burden data (incidence and prevalence), macronutrient supply and gross domestic product (GDP) were collated from more than 150 countries from 1990 to 2018 and analyzed with nutritional geometric framework generalized additive mixed models (GAMMs).ResultsModeling results suggested the interactive effects of food environment and socioeconomic status on ADHD. Fat supply, especially plant-based fat supply, is associated with decreased ADHD prevalence and incidence. These associations were conserved across sexes and ages. They were not confounded by the total energy supply.ConclusionGlobally, fat, particularly plant-based fat supply in food environment correlated with the reduction of ADHD prevalence and incidence, implying its potential protective effects. This is supported by previous reports about the amelioration of ADHD with ketogenic diets. Further in-depth studies are needed to elucidate the underlying mechanistic. This might potentially provide some evidence for future targeted dietary interventions for ADHD prevention.